Prospects for Development of Ukraine’s Energy Market as Part of the “Intermarium” Project - PYSAR, NADIIA (Journal of Education, Technology and Computer Science, 2018)
In the globalized world, the issue of establishing new forms of cooperation in Ukraine’s energy sector with the countries of Central Europe is becoming urgent. With this in mind, the prospects of the project of "vertical" economic integration from north to south, from Scandinavia and the Baltic to the Balkan countries with access to the Adriatic Sea have been considered. The project of the Baltic-Black Sea alliance that is made up on the basis of security motives and includes the development of energy cooperation has been analyzed. It has been proven that with its powerful energy potential, Ukraine is able to integrate into the energy space using its own resource base and diversify the supply of fuel and energy resources within the energy space on a competitive basis. The scientific concept of the polarized space for the region’s development with a resource potential for the development of Ukraine’s economy in the context of globalization and European integration has been proposed.